North Atlantic Regional Water Resources Study. Appendix G. Land Use and Management. - ECONOMIC RESEARCH SERVICE WASHINGTON D C (1972)
This Appendix addresses itself to the identification of land capabilities and their location in relation to changing demands. It also identifies the constraints to land use shifts in response to changing demands or a more efficient and/or acceptable distribution of land use. Projections are presented of the changing demand and changing availabilities with and without planned land use changes. In addition, several analyses of the above parameters are presented to identify the various capabilities of the land resource base to provide for the demands placed upon the resource. As shown in the syllabus and chapters to follow, the varying capabilities under alternative assumptions expose problems and solutions about the ability of the land resource base within the NAR to meet the requirements thrust upon it. Current programs are briefly discussed along with their limitations. Capabilities of management programs are assessed leading to recommendations of policies and programs found in the main report. Appendix G to report dated Jun 72, AD-A036 616. See also Appendix H, AD-A036 629. Includes envelope with 1 map.